Impact of economic growth and financial development on renewable energy use in selected oil-exporting countries - Belloumi, Mounir; Aljazea, Ahmed (Asian Journal of Economic Modelling, 2024)
The aim of this study is to explore the influence of economic growth and financial development on renewable energy consumption. For the purpose of analysis, this investigation uses annual data on renewable energy consumption, economic growth, financial development, consumer price index, domestic investment, and foreign direct investment for 13 major oil-exporting countries, including Algeria, Guinea, Gabon, Iran, Libya, Nigeria, Congo, Republic of Venezuela, Saudi Arabia, Mexico, Malaysia, Sudan, and Russia, during the period 1990-2020. The study employs the Pooled Mean Group (PMG) method and Dumitrescu-Hurlin panel causality test to conduct the empirical analysis. The Hausman test determines the PMG estimator as the most suitable among the Mean Group (MG), Dynamic Fixed Effect (DFE), and PMG estimators. This research shows that economic growth and financial development have a positive and significant long-term impact on renewable energy consumption. This suggests that as the economy grows and financial systems develop, there is a potential for an increase in the use of renewable energy. The Dumitrescu-Hurlin causality test and the panel dynamic ordinary least squares (DOLS) method support these findings. From a policy standpoint, promoting economic growth and financial development could lead to greater use of renewable energy and contribute to sustainable development in oil-exporting countries.